Self-monitoring blood pressure in patients with hypertension: an internet-based survey of UK GPs - Fletcher, B; Hinton, L; Bray, E; Hayen, A; Hobbs, R; Mant, J; Potter, J; McManus, R (Royal College of General Practitioners, 2016)
BACKGROUND: Previous research suggests that most GPs in the UK use self-monitoring of blood pressure (SMBP) to monitor the control of hypertension rather than for diagnosis. This study sought to assess current practice in the use of self-monitoring and any changes in practice following more recent guideline recommendations. AIM: To survey the views and practice of UK GPs in 2015 with regard to SMBP and compare them with a previous survey carried out in 2011. DESIGN AND SETTING: Web-based survey of a regionally representative sample of 300 UK GPs. METHOD: GPs completed an online questionnaire concerning the use of SMBP in the management of hypertension. Analyses comprised descriptive statistics, tests for between-group differences (z, Wilcoxon signed-rank, and χ(2) tests), and multivariate logistic regression. RESULTS: Results were available for 300 GPs (94% of those who started the survey). GPs reported using self-monitoring to diagnose hypertension (169/291; 58%; 95% confidence interval (CI) = 52 to 64) and to monitor control (245/291; 84%; 95% CI = 80 to 88), the former having significantly increased since 2011 (from 37%; 95% CI = 33 to 41; P<0.001) with no change in monitoring for control. More than half of GPs used higher systolic thresholds for diagnosis (118/169; 70%; 95% CI = 63 to 77) and treatment (168/225; 75%; 95% CI = 69 to 80) than recommended in guidelines, and under half (120/289; 42%; 95% CI = 36 to 47) adjusted the SMBP results to guide treatment decisions. CONCLUSION: Since new UK national guidance in 2011, GPs are more likely to use SMBP to diagnose hypertension. However, significant proportions of GPs continue to use non-standard diagnostic and monitoring thresholds. The use of out-of-office methods to improve the accuracy of diagnosis is unlikely to be beneficial if suboptimal thresholds are used.